1992
DOI: 10.1111/j.1365-2249.1992.tb07941.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating antibodies to heat-shock protein 60 in Crohn's disease and ulcerative colitis

Abstract: SUMMARYHeat-shock proteins (HSPs) are highly conserved immunogenic intraeellular molecules that are induced by inflammatory mediators and may induce autoimmune phenomena in vivo. We have recently demonstrated the increased expression of HSP-60 in the coionocytes of patients with ulcerative colitis. To study further the rote of HSP-60 in inflammatory bowel disease, we have now measured antibodies to recombinant mycobacterial HSP-65 (a member ofthe HSP-60 family) in patients with Crohn's disease, ulcerative coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…It has been suggested that bacterial Hsp60 (GroEL) can invade the blood from its source in the intestine and induce anti-GroEL antibodies that will crossreact with the human Hsp60 and lead to autoimmune reactions in various tissues, including in the colon mucosa. [56][57][58] Similarly, GroEL could penetrate the mucosal tissue and interact with local macrophages and initiate inflammation, adding to the effect of endogenous Hsp60 freed from stressed and damaged cells. Thus, management of the intestinal flora would be of the essence in the treatment of UC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that bacterial Hsp60 (GroEL) can invade the blood from its source in the intestine and induce anti-GroEL antibodies that will crossreact with the human Hsp60 and lead to autoimmune reactions in various tissues, including in the colon mucosa. [56][57][58] Similarly, GroEL could penetrate the mucosal tissue and interact with local macrophages and initiate inflammation, adding to the effect of endogenous Hsp60 freed from stressed and damaged cells. Thus, management of the intestinal flora would be of the essence in the treatment of UC.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-p43 antibody also identified p43, as a 28 kDa processed product in Western blots of protein extracts from MAP (Tizard et al, 1992). Mycobacterial 65 kDa heat shock proteins (Hsp65) are among the most extensively studied mycobacterial proteins, and their immunogenic characteristics have been suggested to be the basis for autoimmunization in chronic inflammatory diseases (Elsaghier et al, 1992;Stevens et al, 1992;Szewczuk and Depew, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The participation of chaperones in the pathogenesis of autoimmune diseases, including IBD, has been postulated before (Stevens et al 1992;Ludwig et al 1999;Stahl et al 1998;Sukegawa et al 2000;Imamura et al 2005;Kamphuis et al 2005;Nara et al 2008;Puga Yung et al 2009) but information on Hsp60 and Hsp10 localization and levels in mucosal samples from CD and UC patients is scarce, or lacking in the case of Hsp10. The present work aims at filling this gap and, thus, at elucidating whether or not Hsp60 and Hsp10 should be further investigated as possible disease biomarkers useful in diagnosis and prognosis, etiologic-pathogenetic factors, or therapeutic targets in IBD.…”
Section: Introductionmentioning
confidence: 99%